The mycobiomes and bacteriomes of sputum, saliva, and home dust. (7th October 2020) - Niemeier‐Walsh, Christine; Ryan, Patrick H.; Meller, Jarek; Ollberding, Nicholas J.; Adhikari, Atin; Indugula, Reshmi; Reponen, Tiina
Abstract: Respiratory microbiome is an understudied area of research compared to other microbiomes of the human body. The respiratory tract is exposed to an array of environmental pollutants, including microbes. Yet, we know very little about the relationship between environmental and respiratory microbiome. The primary aim of our study was to compare the mycobiomes and bacteriomes between three sample types from the same participants, including home dust, saliva, and sputum. Samples were collected from 40 adolescents in a longitudinal cohort. We analyzed the samples using 16s bacterial rDNA and ITS fungal rDNA gene sequencing, as well as quantitative PCR with universal fungal and bacterial primers. Results showed that home dust had the greatest alpha diversity between the three sample types for both bacteria and fungi. Dust had the highest total fungal load and the lowest total bacterial load. Sputum had greater bacterial diversity than saliva, but saliva had greater fungal diversity than sputum. The distribution of major bacterial phyla differed between all sample types. However, the distribution of major fungal classes differed only between sputum and saliva. Future research should examine the biological significance of the taxa found in each sample type based on microbial ecology and associations with health effects.